2016
DOI: 10.1108/ijge-02-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Becoming an entrepreneur: opportunities and identity transitions

Abstract: Purpose -This paper aims to report an empirically grounded theoretical framework within which to understand the role of entrepreneurial identity development in the discovery, development and exploitation of opportunity, and to elaborate on how these identity transitions both mobilise and constrain female entrepreneurs. Design/methodology/approach -A qualitative case study-based research design was used in this study. Primary and secondary data were collected from eight female participants (all of whom can be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 71 publications
2
42
0
Order By: Relevance
“…Integration is frequently used to deal with work–family conflicts. For example, female entrepreneurs may integrate their business practices with their lifestyles and personal commitments and establish habitual routines to address the tension between being a mother and being a business owner (Lewis, Ho, Harris, & Morrison, 2016). Similarly, business owners may integrate themselves into the family as a way to release emotional tension, find social support, or facilitate relationships (Knapp et al, 2013).…”
Section: Management Of Family-related Conflictsmentioning
confidence: 99%
See 2 more Smart Citations
“…Integration is frequently used to deal with work–family conflicts. For example, female entrepreneurs may integrate their business practices with their lifestyles and personal commitments and establish habitual routines to address the tension between being a mother and being a business owner (Lewis, Ho, Harris, & Morrison, 2016). Similarly, business owners may integrate themselves into the family as a way to release emotional tension, find social support, or facilitate relationships (Knapp et al, 2013).…”
Section: Management Of Family-related Conflictsmentioning
confidence: 99%
“…Second, learning often requires behavior change, and change may trigger resistance and provoke new conflicts. For example, Lewis et al (2016) find that women pursue entrepreneurship as a way to deal with work–family conflict. However, these businesswomen have to deal with new conflicts that resulted from the identity transition from a mother to a “mompreneur.”…”
Section: Management Of Family-related Conflictsmentioning
confidence: 99%
See 1 more Smart Citation
“…The words 'family' and 'women' are very closely related to each other even when it comes to entrepreneurship. There is a strong link between female entrepreneurship and the prevailing family systems (Welsh et al, 2016) in which identity enactment is observed by embedding habitual routines into their business practices (Lewis, Ho, Harris, & Morrison, 2016). Researchers have concluded generally that women have different aspirations and non-pecuniary motives for pursuing entrepreneurship, as well as a greater need to gain flexibility for balancing work and family responsibilities (Minniti & Naudé, 2010).…”
Section: Figure 1 Ascher (2012)'s Conceptual Modelmentioning
confidence: 99%
“…However, masculine and feminine entrepreneurial identities are more complex than the universalistic explanation of patriarchy may suggest (Hamilton, 2006). Studies find that the level of conflict experienced by women in the construction of their entrepreneurial identities is not uniform, but could be influenced by their social status (Garcia & Welter, 2011), the role conflicts arising from life transitions (Lewis, Ho, Harris & Morrison, 2016), their geographical locations (Pettersson & Heidt, 2014) or socio-cultural contexts (Leung, 2011).…”
Section: Identity Workmentioning
confidence: 99%